2023
DOI: 10.1093/cid/ciad032
|View full text |Cite
|
Sign up to set email alerts
|

The Infectious Diseases Society of America Guidelines on the Diagnosis of COVID-19: Antigen Testing (January 2023)

Abstract: Background Immunoassays designed to detect SARS-CoV-2 protein antigens (Ag) are commonly used to diagnose COVID-19. The most widely used tests are lateral flow assays that generate results in approximately 15 minutes for diagnosis at the point-of-care. Higher throughput, laboratory-based SARS-CoV-2 Ag assays have also been developed. The number of commercially available SARS-CoV-2 Ag detection tests has increased rapidly, as has the COVID-19 diagnostic literature. The Infectious Diseases Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 119 publications
0
35
0
Order By: Relevance
“…SARS-CoV-2 antigen nasal swab, confirmed with rt-PCR test, was used to confirm infection at treatment baseline and to assess viral clearance. 11 Antigen test was preferred to PCR at screening since it has been described to better correlate with viral culture. 12 One patient was asymptomatic for SARS-CoV-2 infection, with a persistent antigen positivity at nasal swab in the last 9 months, confirmed by both RT-PCR and viral culture tests, but with urgent need of immuno-chemotherapy due to pulmonary involvement of diffuse large B-cell lymphoma.…”
Section: Dual Antiviral Therapy In Haematological Patients With Protr...mentioning
confidence: 99%
“…SARS-CoV-2 antigen nasal swab, confirmed with rt-PCR test, was used to confirm infection at treatment baseline and to assess viral clearance. 11 Antigen test was preferred to PCR at screening since it has been described to better correlate with viral culture. 12 One patient was asymptomatic for SARS-CoV-2 infection, with a persistent antigen positivity at nasal swab in the last 9 months, confirmed by both RT-PCR and viral culture tests, but with urgent need of immuno-chemotherapy due to pulmonary involvement of diffuse large B-cell lymphoma.…”
Section: Dual Antiviral Therapy In Haematological Patients With Protr...mentioning
confidence: 99%
“…However, during periods of low COVID-19 prevalence, the positive predictive value decreases, and falsely positive test results may lead to unnecessary isolation among hospitalized patients or unnecessary delays in surgery. 5,6,34,35 Also of concern are false-negative results, which can occur especially with antigen tests in asymptomatic persons. A systematic review reported a pooled sensitivity of 81% (95% CI, 78%-84%) for antigen test detection of SARS-CoV-2 compared to standard nucleic acid amplification testing.…”
Section: Test Performancementioning
confidence: 99%
“…[1][2][3][4][5][6] Indeed, Ag-RDTs are a powerful tool given the low cost (compared with molecular tests), speed, and portability-all of which improve accessibility in remote or lower-resourced settings and at-home use. 5,7,89 However, Ag-RDTs and some rapid molecular tests have lower analytical sensitivity than most gold-standard reverse-transcription quantitative PCR (RT-qPCR) tests and therefore require high viral loads (typically greater than 10 5 copies/mL) to reliably yield positive results. 7,8,[10][11][12][13][14][15][16][17][18] Further, Ag-RDTs are frequently used in unintended ways.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,89 However, Ag-RDTs and some rapid molecular tests have lower analytical sensitivity than most gold-standard reverse-transcription quantitative PCR (RT-qPCR) tests and therefore require high viral loads (typically greater than 10 5 copies/mL) to reliably yield positive results. 7,8,[10][11][12][13][14][15][16][17][18] Further, Ag-RDTs are frequently used in unintended ways. 15,19 For example, although many Ag-RDTs are not authorized for asymptomatic use and/or have poor clinical sensitivity in asymptomatic populations [20][21][22][23] they are widely used for test-to-enter and serial-screening purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation